Geochemical investigation of stream sediments from the nlonako area; littoral, Cameroon: implications for Au, Ag, Cu, Pb and Zn mineralization potentials - Gus Djibril, Kouankap nono; Aloysius, Afahnwie Ngambu; Patrice Arnaud, Kouske; Pierre, Wotchoko; Jonas Didero, Takodjou Wambo; Christopher, Agyingi Mbaringong; Rene, Amie Anzah; Emmanuel, Cheo Suh (International Journal of Advanced Geosciences, 2016)
Nlonako area belongs to Cameroon Volcanic Line. To determine the mineralization potentials of the area, stream sediment survey and geochemistry were carried out. The results show weak anomalies in Gold and Silver with threshold values of 0.001 and 0.073 respectively. Copper, Lead and Zinc have some relatively high values which are 690ppm, 182ppm and 378ppm with mean values statistically calculated to be 73.90, 46.51 and 198.58 respectively. The data analyzed using multivariate statistical methods yielded 5 factors from Principal Component Analysis (PCA). These five factors are; Factor 1 (Ce, La, Nb, Y), Factor 2 (W, Mo, Sr, As, Cd, Ni), Factor 3 (Pb, Sn, Zn, Sb), Factor 4 (Au, Ag, Cu) and Factor 5 (Cr, Co, Bi). These factors point mostly to a possible sulphide mineralization. Gold shows high correlation with Ag and Cu while Y correlates more highly and positively with Ce and La. There is a relatively high input of the light rare-earth elements which form the highest factor (34.363%) of the total PCA variance and possibly points to a granitic source rock. The existence of mafic–ultramafic igneous rocks in the study area underlies high correlations between Cr and Co and other factors gotten from PCA.